Development of novel polymer (stearyl acrylate-cobehenyl acrylate) for wax deposition inhibition of malaysian crude oil - Norida, Ridzuan; M. Elarbe, Basem Saied; Elganidi, Ibrahim; Devi, V. Shamala (2021)
SABA PPD copolymer was synthesized by different monomers which are stearyl acrylate (SA) and behenyl acrylate (BA) using a free radical solution polymerization method as a novel polymeric pour point depressant (PPD).